Exploring and analyzing mathematics learning activities through a constructivist approach: A case study - Dwi Permatasari; Tahir Tahir; Chairuddin Chairuddin (Psychology, Evaluation, and Technology in Educational Research, 2025)
This study aims to explore and analyze the application of a constructivist approach in mathematics learning at SMA Negeri 1 Lalolae. The research employed a descriptive qualitative method with data triangulation through classroom observations, teacher interviews, and student questionnaires. The findings indicate that constructivist elements have been partially implemented, as reflected in classroom discussions, opportunities for students to express arguments, and activities that encourage independent problem solving. Students showed positive responses in terms of increased motivation and learning engagement, although some students remained passive and experienced difficulties in constructing concepts independently. In conclusion, the implementation of a constructivist approach in mathematics learning at SMA Negeri 1 Lalolae has not yet been optimal and requires support in the form of improved learning facilities and teacher training to enhance its effectiveness and sustainability.